ISLAM RAḤMATAN LI ’L-‘ĀLAMĪN SEBAGAI LANDASAN DAKWAH MULTIKULTURAL: PERSPEKTIF MUHAMMAD FETHULLAH GÜLEN - Achmad Bisri (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2014)
This article aimed to analyze Fethullah Gülen’s concept on raḥmatan li ’l-‘ālamīn. This concept can be used as an important basic for designing a multicultural da‘wa that emphasizes: (1) love and affection; (2) tolerance; and (3) interfaith dialogue. This research used hermeneutic analysis. There are three important research findings. Firstly, Islam as raḥmatan li ‘l-‘ālamīn to be reflected with love and affection. Secondly, Islam as raḥmatan li ’l-‘ālamīn to be reflected with interfaith dialogue. Thirdly, Islam as raḥmatan li ’l-‘ālamīn to be reflected as tolerance.